ANALISIS EFISIENSI TEKNIS USAHA TAMBAK UDANG VANNAME PETAMBAK MANDIRI EKS PLASMA PT CENTRALPERTIWI BAHARI DI KABUPATEN TULANG BAWANG - Ristiana Restuti; Fembriarti Erry Prasmatiwi; Wuryaningsih Dwi Sayekti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to determine the level of income of vanname shrimp cultivatiors and analyze the level of technical efficiency and factors that affect the technical efficiency of vanname shrimp farming in the Bratasena Adiwarna Village, Dente Teladas Subdistrict, Tulang Bawang Regency.  The samples in this study were 70 cultivators chosen using simple random sampling method. Data were collected in February - March 2018.  Technical efficiency analysis was tested using the frontier production function, while factors affecting technical efficiency were tested using the exponential function. The results showed that the average income of shrimp cultivation is IDR22,533,081.50 per 0.49 ha of ponds. Vanname shrimp farming is technically efficient with a level of 84.59.  Factors affecting technical efficiency are age and cultivation experience with a 90% confidence level. Key words: cultivators, efficiency, vanname shrimp